Comparison of the effectiveness of StyleWriter and Microsoft Word computer software to improve English writing skills - Prvinchandar, Sunita (Canadian Center of Science and Education, 2014)
This study compared the effectiveness of two types of computer software for improving the English writing skills of pupils in a Malaysian primary school. Sixty students who participated in the seven-week training course were divided into two groups, with the experimental group using the StyleWriter software and the control group using the Microsoft Word programme. A pre-test was administered before the experiment was conducted. This was followed by post-tests upon completion of the course, where a computer-based assessment, as well as a pen-and-paper assessment, was employed. In each test, four components of writing skills were assessed, namely grammar, vocabulary, spelling, sentence structure, besides the overall performance. The findings indicated that the students who were exposed to StyleWriter had significantly better scores in all the writing components compared to the control group using Microsoft Word in both pen-and-paper and computer-based essay writing assessments. This study showed that StyleWriter enhanced the students’ writing skills even when computer assistance was no longer available.